The impact of strategy training on strategy use and reading in L3 Spanish: The results of a ten-month study of 11-year-old learners - Chrobak, Dominika (Neofilolog, 2025)
In today’s competitive and globalized world, in which plurilingualism is the norm, many students learn not just one, but two foreign languages in the primary school. One of the ways to facilitate L3 learning is to enable learners to refer to their prior experience, and show them how they can use prior language knowledge (usually the mother tongue and English) to their advantage. The aim of this paper is to present the results of a pre-test post-test study investigating what impact a programme of strategy training had on 11-year-old learners’ reading strategy use and reading ability in L3 Spanish. The intervention included cognitive, metacognitive and affective strategies. The data was collected by means of think aloud protocols, strategy questionnaires and reading tests. The results of the study suggest that after the training learners still employed a limited number of strategies, which may be attributed to their developing metalinguistic awareness. Yet, strategy training positively impacted the overall reading test performance of high- and average-achieving students, but not those who were low achieving.